IMPLEMENTASI LOAD BALANCING UNTUK PENINGKATAN LAYANAN VOIP BERBASIS SIP - ANDY, MARTINUS
Today, VoIP is more widely used due to its advantage in cost reduction. This event causes the ever-increasing VoIP traffic which will directly implicate the increasing of load controlling demand. To solve this problem, load balancing can be used so that the system can distribute overall load to every VoIP server which interconnects each other. The implementation of load balancing requires one computer which functions as a load balancer and two more computers which functions as the real servers. The Load balancer does its function by selecting one of the VoIP servers in the network using a specific algorithm and then forwards the client request so that the server can process it. In this final project, the VoIP signaling protocol which is used for the load balancing purpose is SIP. To facilitate the SIP load balancing function, software called OpenSIPS is used. OpenSIPS is a SIP Proxy that has additional function which is balancing load throughout the network. Testing is taken by trying the failover / backup server feature. It is done by testing if a server suffers failure, other servers can take the role and function of the failed one for temporary until the failed server can restore its function again. Additionally, measurement for maximum call rate before call loss occured is also taken before and after load balancing implemented. Last, measurement for delay and jitter for various call rates is taken. The result is after the first server exceeds 142 calls per second and the second server exceeds 150 calls per second, both experiences call loss and the significant increase of delay and jitter. When load balancing is implemented, system experiences call loss and significant increase of delay and jitter after exceeding 293 calls per second. Thus, load balancing improves performance and QoS of the system.